Lateral ultrasound-guided axillary RUMM block in cats: a pilot cadaveric study. Issue 4 (April 2021) - Pratt, Shaun B; Martinez-Taboada, Fernando
Objectives: This study aimed to describe the prominent landmarks for an in-plane ultrasound-guided lateral approach to an axillary RUMM block in cats and document the anatomical distribution of injected solution in cadavers. Methods: Eleven mixed breed, frozen-thawed cat cadavers were used. The ultrasound probe was placed on the lateral aspect of the forelimb. A spinal needle was used to inject either methylene blue 5 mg/ml or permanent tissue dye 1:10 within the focal clustering point of the radial (R), ulna (U), median (M) and musculocutaneous (Mc) nerves. The block was approached from either a cranial or caudal direction. Specimens were immediately dissected. A successful block was defined as ⩾20 mm of continuous stain on all nerves (R, U, M and Mc), a partial block as one or more nerves stained ⩾20 mm continuously and a negative block failed to stain any nerve ⩾20 mm. Results: The cranial approach stained the R 8/9, U 6/9, M 6/9 and Mc 8/9 nerves successfully, while the caudal approach stained the R 7/9, U 8/9, M 7/9 and Mc 5/9 nerves successfully. There were no statistical differences on staining rates between approaches or limbs used. Conclusions and relevance: The lateral approach to an axillary RUMM block is feasible in cats and may be a useful alternative to current approaches used for brachial and antebrachial desensitisation. Both cranial and caudal approaches produced similar results; however, further research in live animals will determine the clinical applicability.